Green Brazilian propolis action on macrophages and lymphoid organs of chronically stressed mice - Missima, Fabiane [UNESP]; Sforcin, Jose Mauricio [UNESP] (Oxford University Press, 2008)
Stress is a generic term that summarizes how psychosocial and environmental factors influence physical and mental well-being. The interaction between stress and immunity has been widely investigated, involving the neuroendocrine system and several organs. Assays using natural products in stress models deserve further investigation. Propolis immunomodulatory action has been mentioned and it has been the subject of scientific investigation in our laboratory. The aim of this study was to evaluate if and how propolis activated macrophages in BALB/c mice submitted to immobilization stress, as well as the histopathological analysis of the thymus, bone marrow, spleen and adrenal glands. Stressed mice showed a higher hydrogen peroxide (H2O2) generation by peritoneal macrophages, and propolis treatment potentiated H2O2 generation and inhibited nitric oxide (NO) production by these cells. Histopathological analysis showed no alterations in the thymus, bone marrow and adrenal glands, but increased germinal centers in the spleen. Propolis treatment counteracted the alterations found in the spleen of stressed mice. New research is being carried out in order to elucidate propolis immunomodulatory action during stress.
Keywords: lymphoid organs; macrophages; propolis; stress